Dialogismo e polifonia nas vozes severinas - Lopes, Luiz Fernando Silva (2016)
This research descriptive and analytical, qualitative discusses the theories of the Russian philosopher Mikhail Bakhtin regarding the dialogic and polyphony in the poem Morte e Vida Severina, of João Cabral de Melo Neto. We aimed to analyze the dialogic and polyphonic categories of some stanzas of that poem, specifically, the subject as a representation of a social collective, intertextuality and poetic intergenericidade because we believe that this guy is an inseparable part of the things of the world and the things that surround. Our theoretical framework was made from Bakhtin's ideas (1998, 2005, 2011); and the Voloshinov in respect of discourse aspects, and Candido ideas (2010) of Secchin (2003), Teles (1977) and Cabral itself (2015), with regard to literary aspects. Our analysis points to the study of discursive dialogism present in the poem and its discursive marks that intertwine with historical, cultural and ideological values, featuring thus a text with great discursive richness. The presence of polyphony is another brand present in this study indicating the formation of social subjects that reflect a community of discourse, always open to multiple possibilities, whose characters being pointed in an unfinished process of evolution. This concept shall be taken in poem analysis as the position taken by the narrator - character-as a conductor of a large chorus of voices participating in the aesthetic construction. The intertextual relations are also part of our research, and it was possible to find them in the presence of elements of medieval and religious culture, which, quite influenced cabralinos writings, beyond the aspects of folklore and popular culture; all in line with the development of the poem. Finally, the multiple aspect of corpus analysis also shows up in the intergeneric relationships, because it is a theatrical text made in verse, which characterizes it as a dramatic poem.